A mechanistic oxygen- and temperature-limited metabolic niche framework. (17th June 2019) - Ern, Rasmus
Abstract : The abundance and distribution of fishes and other water-breathing ectotherms are partially shaped by the capacities of individuals to perform ecologically relevant functions, which collectively determine whole-organism performance. Aerobic scope (AS) quantifies the capacity of the cardiorespiratory system to supply tissues with oxygen for fuelling such functions. Aquatic hypoxia and water temperature are principal environmental factors affecting the AS of water-breathing ectotherms. Although it is intuitive that animal energetics will be of ecological significance, many studies argue against a hypothesized overarching link between AS, whole-organism performance, and shifts in the abundance and distribution of water-breathing ectotherms with environmental change. Consequently, relationships between AS and ecologically relevant performance traits must be established for individual species. This article proposes a mechanistic framework for integrating and correlating experimental traits for assessing the AS, anaerobic capacity (AC) and range boundaries of water-breathing ectotherms exposed to progressive aquatic hypoxia and rising water temperature. The framework also describes cardiorespiratory thermal tolerance and proposes an empirical definition of the mechanism underlying the critical thermal maximum in species with oxygen-dependent upper thermal limits. Incorporating performance traits, exemplified with preference and avoidance responses, may provide information about the role of metabolism in shaping whole-organism performance, and the potential applicability of AS and AC in species distribution models. This article is part of the theme issue 'Physiological diversity, biodiversity patterns and global climate change: testing key hypotheses involving temperature and oxygen'.